2020
DOI: 10.7554/elife.62816
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for effector transmembrane domain recognition by type VI secretion system chaperones

Abstract: Type VI secretion systems (T6SSs) deliver antibacterial effector proteins between neighboring bacteria. Many effectors harbor N-terminal transmembrane domains (TMDs) implicated in effector translocation across target cell membranes. However, the distribution of these TMD-containing effectors remains unknown. Here, we discover prePAAR, a conserved motif found in over 6000 putative TMD-containing effectors encoded predominantly by 15 genera of Proteobacteria. Based on differing numbers of TMDs, effectors group i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 69 publications
(76 reference statements)
4
52
0
Order By: Relevance
“…RhsA forms a cocoon-like structure that undergoes a double autocleavage We previously demonstrated that a fragment of RhsA lacking its N-terminal prePAAR motif and two predicted transmembrane helices of the TMD (Figure 1C, residues 74-1486), RhsA∆NT, is stable in the absence of its EagR1 chaperone and can be purified to homogeneity as a soluble protein when over-expressed in Escherichia coli 14 . We therefore expressed and purified RhsA∆NT (Supplementary Figure 1A) and used it for cryo-EM and single particle analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RhsA forms a cocoon-like structure that undergoes a double autocleavage We previously demonstrated that a fragment of RhsA lacking its N-terminal prePAAR motif and two predicted transmembrane helices of the TMD (Figure 1C, residues 74-1486), RhsA∆NT, is stable in the absence of its EagR1 chaperone and can be purified to homogeneity as a soluble protein when over-expressed in Escherichia coli 14 . We therefore expressed and purified RhsA∆NT (Supplementary Figure 1A) and used it for cryo-EM and single particle analysis.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate how RhsA is mounted onto VgrG1 we set out to determine the structure of the secretion competent pre-firing complex (PFC) comprising VgrG1 in complex with fulllength RhsA and EagR1. We purified the complex as described previously 14 and examined it by single particle cryo-EM. The 2D class averages enabled us to unequivocally characterize the arrangement of the subunits of the complex (Figure 5A).…”
Section: Architecture Of the Pre-firing Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, these short toxins might be loaded into other bacterial secretion systems using adaptor proteins, a phenomenon which is known in many secretion systems 5,[53][54][55][56][57][58][59] .…”
Section: Discussionmentioning
confidence: 99%